Using Social Psychology Principles to Develop Emotionally Intelligent Healthcare Leaders - Grunberg, Neil E.; McManigle, John E.; Barry, Erin S. (Frontiers in Psychology, 2020)
Healthcare providers must acquire extensive knowledge and skills to help promote physical health, behavioral health, and wellness; prevent and treat illnesses and injuries; encourage and guide rehabilitation; counsel and assist with decisions relevant to health, life, and death. In addition, 21st Century healthcare providers must develop leadership knowledge and skills to optimize their interactions and effectiveness with healthcare teams, patients, and patients’ significant others. Emotional intelligence is recognized as an essential component of leader education and development. It is important to optimally educate and develop healthcare providers with regard to components of emotional intelligence: self-awareness, self-regulation, social-awareness, relationship regulation. Self-awareness focuses on understanding one’s own behaviors, cognitions, motivations and emotions. Self-regulation emphasizes self-control and adaptability to various situations and settings. Social awareness includes understanding others’ behaviors, cognitions, motivations and emotions. Relationship regulation draws upon the other components of emotional intelligence in order to optimize collaboration and cooperation and attainment of mutual goals with other people. The present paper presents four principles of Social Psychology that are relevant to developing emotionally-intelligent healthcare leaders: Field Theory, Informal Social Communication, Social Comparison, and Cognitive Dissonance. Although these principles are well-established and have received extensive attention, analysis, and discussion in the academic social psychology literature, they are rarely mentioned in the emotional intelligence or leadership literatures. Therefore, each of these principles is briefly described in the present paper followed by an explanation of how each principle relates to the development of emotional intelligence in general and to emotionally-intelligent healthcare leaders in particular.